REGULATORY MECHANISMS OF HUMAN MONOCYTIC THP-1 CELLS TRANSENDOTHELIAL MIGRATION INDUCED BY STREPTOCOCCUS PYOGENES COMPONENTS - E. A. Starikova; A. M. Lebedeva; N. A. Aktureeva; L. A. Burova; I. S. Freidlin (Медицинская иммунология, 2014)
Abstract. Enhanced transendothelial migration of leukocytes during infection and inflammation occurs due to increased expression of ICAM-1 and VCAM-1 adherence molecules of the immunoglobulin superfamily, and increased secretion of chemokines by endothelial cells. Our previous in vitro studies with human monocytic THP-1 cells showed that some components of Streptococcus pyogenes caused a sufficient enhancement of transendothelial cell migration. However, expression levels of adhesion molecules remained unchanged on endothelial cells. The purpose of the work was to study mechanisms underlying the enhanced transendothelial migration of THP-1 cells treated with supernatante of streptococcal cells (SSC). SSC exhibited chemoattractive activity towards THP-1 cells. SSC increased chemotaxis and transmigration of THP-1 cells. Meanwhile, a 24-hour preincubation of THP-1 cells with SSC caused suppression of the both effects, being accompanied by decreased level of Focal Adhesion Kinase phosphorylation. Preincubation of THP-1 cells with pertussis toxin did reduce the transmigration intensity in presence of the SSC down to the level of spontaneous migration. These results suggest that increased transmigration of THP-1 cells under the influence of SSC may be determined by its chemoattractive action upon the migrating cells.